Creative Product Innovation and Appropriate Technology: Transforming Santri Skills In The Digital 4.0 Era - Khalil Aziz (CV Putra Publisher, 2026)
Modern pesantren (Islamic boarding schools) are no longer limited to their traditional role as centers of religious learning but are increasingly functioning as hubs for creative product innovation and appropriate technology (AT) development. While previous studies have primarily focused on entrepreneurship training and vocational education in pesantren, this study offers a distinct contribution by integrating Project-Based Learning (PjBL) with appropriate technology and digital product innovation as a systematic strategy for transforming santri competencies in the Digital 4.0 era. This article aims to analyze how pesantren develop santri skills in producing both physical and digital products with functional value, economic relevance, and market competitiveness. Using a qualitative descriptive approach supported by PjBL implementation, santri were engaged in solving local community problems through practical innovations such as food-processing tools, eco-friendly products, digital marketing systems, and simple software applications. The findings reveal that this model significantly improves santri competencies in problem-solving, technological adaptation, entrepreneurial mindset, and collaborative work skills. In addition, pesantren experienced increased institutional economic independence through productive business units managed by santri. This study contributes to the discourse on Islamic education transformation by proposing an integrative model of religious learning, technological innovation, and sustainable economic empowerment within pesantren institutions.